'Now try and recollect if you have done any good today'. Household, individual and community in the early fiction of Harriet Martineau, c. 1825-41. - Warren, JB (2013)
A re-evaluation of the early fiction of Harriet Martineau (1802-76) is timely. In failing to interrogate the reciprocity between Martineau’s interpretation of personal experience and her fiction, scholars have not fully appreciated its purpose. Thus, modern criticism has accepted Martineau’s dismissive judgement of her earliest tales. Five Years of Youth (1831) has been labelled a pastiche of Jane Austen, and the Illustrations of Political Economy (1832-4), which established Martineau’s fame, have also been subject to bruising attack – as poor art, and ideologically mendacious. Most scholars see the novel Deerbrook (1839) as a conventional romance. Although Linda Peterson and Lana Dalley rightly identify in Martineau’s fiction the trope of domesticity and its political dimension, the argument of this thesis is more specific. Message and discourse, whether couched as political economy, children’s adventure or romance, were shaped by Martineau’s ‘heartland concepts’. The product of her subjectivity, these core values were a sense of duty (initially allied to a previously-unacknowledged soteriology of ‘safety’); a welcome offered to adversity as a stimulus to progress; an attack on superstition as an enemy to intellectual and moral progress; and household relationships which were inclusive of children and servants and stimulated community engagement. Martineau’s definition of community, predicated on a sense of belonging, initially reflected the networking of her Norwich household. It was subsequently redefined as wherever her own household could meet a local need. This interpretation is supported by an analysis of Martineau’s engagement with her adopted community of Ambleside, where, in putting into practice her fictional teachings, she demonstrated reciprocity in action.